EFEKTIVITAS PENGGUNAAN GAMBAR PADA BROSUR DALAM MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR FISIKA KELAS XI SMAN 5 PADANG - Ulil Kurnia; Hamdi Rifai; Nurhayati Nurhayati (Universitas Negeri Padang, 2015)
Learning model that is less engaging students in the learning process and the low reading interest of students make the learning process runs less effective. It is characterized by student learning outcomes that are lower than the expected maximum graduation criteria. To overcome these problems, the use of media images on brochures learning model applied in problem based learning. The Type of this research is quasi experiment with design is randomized control group only. Population of this research is all class XI MIA who registered in the 1st half 2014/2015 academic year. Samples were taken at random cluster sampling technique. The research instrument are the ultimate test for cognitive, observation format, self assessment sheet and peer assessment sheet for affective domain of learning outcomes, and performance assessment rubric and portofolio assessment sheet for psychomotor learning outcomes. The results showed that the average outcomes of learning physics class experiment better than the control class for the third domain of the real level of 0.05. This indicates that the picture effectively used to improve student learning outcomes physics